2017
DOI: 10.1111/jocn.14173
|View full text |Cite
|
Sign up to set email alerts
|

Exploring communication during the journey from noticing bodily changes to a diagnosis of endometrial cancer

Abstract: Women and some health professionals may be unfamiliar with symptoms potentially indicative of endometrial cancer. There may be structural and communication barriers for women navigating healthcare systems. It is vital that nurses take time both to listen to women and to provide them with resources to enhance their health literacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 46 publications
(76 reference statements)
1
34
0
Order By: Relevance
“…38 Interviews were conducted within 9 months of diagnosis, with the authors finding participants had limited knowledge of oesophageal cancer, initially appraising symptoms in the context of normal bodily functions until symptoms changed or worsened. This reflects findings in the current study, and resonates with research across other cancers, where subtle or intermittent symptoms are often not considered serious [25][26][27][39][40][41] and initial bodily changes are attributed to benign causes. 39,[42][43][44][45] Another study explored the use of over-the-counter medication in Scotland with 25 patients diagnosed with lung (n = 14), colorectal (n = 4), or oesophago-gastric (n = 7) cancer in the preceding 12 months.…”
Section: Comparison With Existing Literaturesupporting
confidence: 81%
“…38 Interviews were conducted within 9 months of diagnosis, with the authors finding participants had limited knowledge of oesophageal cancer, initially appraising symptoms in the context of normal bodily functions until symptoms changed or worsened. This reflects findings in the current study, and resonates with research across other cancers, where subtle or intermittent symptoms are often not considered serious [25][26][27][39][40][41] and initial bodily changes are attributed to benign causes. 39,[42][43][44][45] Another study explored the use of over-the-counter medication in Scotland with 25 patients diagnosed with lung (n = 14), colorectal (n = 4), or oesophago-gastric (n = 7) cancer in the preceding 12 months.…”
Section: Comparison With Existing Literaturesupporting
confidence: 81%
“…Half of the included studies identified general health literacy as a barrier to accessing care for AUB [12,15,19,[21][22][23]. One American study in 2010 noted the variability in 71 women in the perception of heavy and irregular bleeding [19].…”
Section: Theme 1: Health Literacymentioning
confidence: 99%
“…In a study of women previously diagnosed and treated for endometrial cancer [22], general uterine health and Pap smears were confused. Many women were upset that their routine cervical smear did not pick up EC:…”
Section: Theme 1: Health Literacymentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, while the risk of endometrial cancer is age-dependent (around 90% of the cases affect women above 45 years), the global rise in obesity increase the incidence in women under the age of 40 (Cook et al 2018;Reeves et al 2007).…”
Section: Introductionmentioning
confidence: 99%